Ekstrak Hibiscus rosa-sinensis L. Memperbaiki Kadar Glukosa Darah Puasa dan Jumlah Sel Mast pada Model Tikus Diabetes Terinfeksi Mycobacterium tuberculosis: Hibiscus rosa-sinensis L. Extract Improves Fasting Blood Glucose Levels and Number of Mast Cells in Diabetic Rat Model that Infected with Mycobacterium tuberculosis - Pakaya, David; Dewi, Marzela; Antari, Arlita Leniseptaria; Saraswati, Indah (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2020)
Background: The condition of hyperglycemia in Diabetes mellitus (DM) causes a disruption of the function of phagocytes that can facilitate M. tuberculosis infection. Immunostimulant from natural ingredients can help improve the condition of hyperglycemia an immune function. Objective: To analyze the effect of Hibiscus rosa-sinensis L. extract on fasting blood glucose level and the number of mast cell in TB-DM mouse model. Methods: This experimental study used 27 male Wistar rats, 8 weeks of age, 200-230 g weight, divided into 3 groups, K: Normal control group, P1: TB-positive mouse group P2: Group rat TB-DM + Hibiscus rosa-sinensis L extract dose 250 mg/kgBW and 3 time measurement of H + 7 DM, H + 14 DM and H + 21 DM. TB-DM model mice were prepared with the administration of nicotinamide (NA) 100 mg/kgBW and streptozotocin (STZ) 65 mg/Kg BW, TB agent 1.5 x 105 CFU. Fasting blood glucose levels were measured by GOD-PAP method and Pulmonary tissue is excised, made in paraffin blocks and stained with blue Toluidine to count the mast cells. Results: There was an improvement in the mean fasting blood glucose levels in the group treated with the Hibiscus rosa-sinensis L. extract of 250 mg/kgBW compared to the TB-DM group without extract therapy followed by decreased the number of mast cell. Conclusion: Hibiscus rosa-sinensis L. extract. improves fasting blood glucose levels and decreases the number of mast cell of TB-DM rat model.